Prilaku Penistaan Agama dalam Struktur Budaya Politik Lokal Pada Kerajaan Islam di Jawa (Sebuah Telaah Politik Hukum) - Kamsi, Kamsi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Blasphemy problems are issues that have emerged in the archipelago long before the republic independence, for example, in the Kraton Kasunanan Surakarta or other kingdoms. The problem up to now always appear in public spaces, and along with that then there are also efforts to resolve the various forms of regulation according to the situation and condition of the development of society, ranging from the shape of legislation to discharge Fatwa Indonesian Ulema Council (MUI). This paper attempts to examine the behavior of blasphemy from the standpoint of legal or political dimension. By using this approach is expected to gain a clearer perspective and basic. In addition, this study tried to find the complex relationships between the dimensions of understanding inherent in the system of belief (belief system) in people with political interests and realities of the developmental needs of society at that time. Perpetrators of blasphemy in the Islamic kingdom in Java kelindan linked with local political structures. Local political structure is very determinant in determining the legal person or group.